Impact of transjugular intrahepatic portosystemic shunt implantation on liver perfusion measured by volume perfusion CT - Preibsch, Heike; Spira, Daniel (Acta radiologica, 2017)
Background: Implantation of a transjugular intrahepatic portosystemic shunt (TIPS) induces changes of liver perfusion.PurposeTo determine the changes in arterial, portal venous, and total perfusion of the liver parenchyma induced by TIPS using the technique of volume perfusion computed tomography (VPCT) and compare results with invasively measured hepatic intravascular pressure values.Material and MethodsVPCT quantification of liver perfusion was performed in 23 patients (mean age, 62.5?±?8.8 years) with portal hypertension in the pre-TIPS and post-TIPS setting, respectively. A commercially available software package was used for post-processing, enabling separate calculation of the dual (arterial [ALP] and portal venous [PVP]) blood supply and additionally of the hepatic perfusion index (HPI) (HPI?=?ALP/(ALP?+?PVP)*100%). Invasive pressure measurements were performed during the intervention, before and after TIPS placement. Liver function tests performed before and after the procedure were compared.ResultsMean decrease of pressure gradient through TIPS was 13.3?mmHg. Mean normal values for ALP, PVP, and total perfusion (ALP?+?PVP) before TIPS were 15.9, 37.7, and 53.5?mL/100?mL/min, respectively, mean HPI was 35.4%. After TIPS, ALP increased to a mean value of 37.7?mL/100?mL/min, PVP decreased (15.7?mL/100?mL/min, P?